A case of TAFRO syndrome successfully treated with cyclosporin A and tocilizumab. Issue 2 (3rd July 2018) - Asano, Tomoyuki; Yashiro, Makiko; Watanabe, Aya; Sato, Shuzo; Kobayashi, Hiroko; Watanabe, Hiroshi; Ohkawara, Hiroshi; Murakami, Fumi; Hashimoto, Yuko; Koga, Tomohiro; Kawakami, Atsushi; Migita, Kiyoshi
Abstract: TAFRO syndrome is a rare constellation of symptoms including thrombocytopenia, anasarca, reticulin myelofibrosis of the bone marrow, renal dysfunction and organomegaly. Although an inappropriate cytokine storm is involved in the pathogenesis of TAFRO syndrome, its etiology is undetermined. Here, we report a case of 46-year-old woman with massive pleural effusion, hepatosplenomegaly and thrombocytopenia. Her clinical features were compatible with TAFRO syndrome according to diagnostic criteria. She showed rapidly progressive pleural effusion and thrombocytopenia. We initially used steroids and cyclosporin A, but its efficacy was limited. Of note, the combined treatment with corticosteroid, cyclosporin A and tocilizumab successfully improved her condition, resulting in disease remission. During the clinical course, an analysis of her serum cytokine profile suggested that several cytokines/chemokines were associated with the development of TAFRO syndrome.